“El valor del respeto en el proceso de enseñanza aprendizaje” - Collaguazo Rodríguez, Cristian David (2023)
The values in the present time are losing a space in the society, generating that the coexistence is not so cordial, and inside the homes creating a series of problems that affects the behavior of the children, the value of the respect in the teaching-learning process was the reason of the investigation. The objective of this study is to analyze the influence of the value of respect in the teaching-learning process of fourth grade students of the Agustín Albán Educational Unit of the Pujilí canton in the school year 2022 - 2023, observing their behavior in the classroom, and the interaction they have with other members of the educational community, demonstrating that values actively intervene in the educational process of the students, allowing them to recognize the qualities of the rights and obligations that they have and the degree of compliance with them, the practice of respect has been related to the school performance of children. A qualitative research was used, which describes the behavior of a social phenomenon, applying the interview as a technique for collecting information, which was applied to the teacher and to a sample of children, evidencing the lack of practice of values in class. Based on the information obtained, the educational unit would need to suggest teaching strategies that encourage the practice of values, which would improve social relations among students and facilitate the work of teachers when teaching their classes